RANCANG BANGUN APLIKASI KATALOG PADA BRAND MANSION CLUB BERBASIS ANDROID - Tri Cahyo, Endar Pradipta; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2025)
This research develops an e-catalog application called Brand Mansion Club to increase the sales profit of a homegrown luxury brand through digitalization. The application showcases exclusive products from Brand Mansion Studio, making It simplifies the process for customers to locate and buy the hight quality product. With innovative features, this application aims to improve marketing efficiency, expand the customer base, and increase sales profit for the homegrown luxury brand.This catalog application was designed for the Mansion Club brand, aiming To simplify user access to information on the products and services offered. Using the Android platform, the application offers an intuitive interface and functionality that allows users to browse and select products efficiently. The Brand Mansion Club application is tailored specifically for Mansion Club, a luxury brand known for its exquisite and exclusive offerings. By leveraging the power of the Android platform, The application offers users an easy-to-navigate, visually appealing, and intuitive interface. Users can quickly browse through the brand’s product catalog, access detailed product descriptions, and make informed purchasing decisions with ease. The app also integrates convenient features such as personalized recommendations, promotional offers, and real-time updates on new product arrivals, ensuring a satisfying and engaging shopping experience.